PENGARUH WAKTU PEMBERIAN DAN KOMPOSISI COMPOST TEA TANDAN KOSONG KELAPA SAWIT DIPERKAYA Azotobacter TERHADAP PRODUKSI SAWI - Jannerson Munthe; Erwin Masrul; T. Sabrina (Universitas Sumatera Utara, 2014)
The demand on organic agriculture products are increasingly with the increasing awareness onhealthy and nutritious foods, and also on protecting environment. In addition, the increasingdemand on organic food caused increasing the demand on organic fertilizers. Compost tea is analternative source of nutrients for plant in order to reduce chemical fertilizers. The aim of this studywas to determine the effect of compost tea application time and composition enriched oil palmempty fruit bunches Azotobacter in increasing the production of mustard. The study used arandomized block design (RBD) factorial consist of 2 factors and 3 replications. The first factor wasthe application time consist of 2 treatments (3 days and 6 days) and the second factor was thecompost tea formula consists of 5 treatments (150 g oil-palm empty fruit bunch compost+ 5000 mLof water, 150 g oil-palm empty fruit bunch compost + 1500 mL of coconut water + 3500 mL ofwater with 2% molasse, 300 g oil-palm empty fruit bunch compost + 3000 mL of coconut water +2000 mL of water with 2% molasse, 150 g oil-palm empty fruit bunch compost + water + 1500mL of coconut water +3500 mL water with 4% molasse and 300 g oil-palm empty fruit bunchcompost + 3000 mL of coconut water + 2000 mL water with molasse 4%). Results showed that theformulation compost tea 300 g oil-palm empty fruit bunch compost with 3000 mL coconut water +2000 mL water + 4% molasse gave the highest mustard production (based on wet weight), dryweight, plant height, leaf width and N uptake by plant and the chlorophyll content in mustard leaf.The best of application time was 6 days which gave the highest yield based on the wet weight, dryweight, plant height, leaf width, and N uptake by mustard. The certain formula of compost tea didnot had to be aplied on certain interval, either every 3 day nor 6 day.Keywords: Oil-Palm Empty Fruit Bunch Compost, compost tea, mustard, coconut water, molasse